Clipping of anterior communicating artery aneurysms in the early post-rupture stage via transorbital keyhole approach—Chinese neurosurgical experience. (3rd September 2015) - Wang, Hui; Luo, Lun; Ye, Zhuopeng; Li, Wensheng; Chen, Chuan; Ba, Yueyang; Ning, Xinjie; Guo, Ying
Abstract : The anterior communicating artery (AComA) complex is the site at which intracranial aneurysms occur most frequently. At present, effective treatments for AComA aneurysms are yet to be developed. Here, we present our experience in successfully managing AComA aneurysms via the transorbital keyhole approach. A total of 52 patients having a history of aneurysm rupture received surgery. All patients were assigned a Hunt–Hess grade prior to surgery. The cistern was opened to expose the AComA complex using a keyhole approach, and aneurysms were then surgically clipped with the assistance of neuroendoscopy or indocyanine green angiography. Surgery outcomes were confirmed using computed tomography angiography (CTA). Each of the 52 AComA aneurysms was successfully clipped with a single operation. Three of these patients experienced intraoperative aneurysm rupture. Five had postoperative hydrocephalus which was successfully treated with ventriculoperitoneal shunt. All patients survived the surgical procedure. Using the Glasgow Outcome Scale scores for evaluation, 39 patients (75.0%) had good recovery, 9 (17.3%) had moderate disability, 2 (3.8%) had severe disability, and 2 patients who had been in preoperative comas (3.8%) remained in a vegetative state. During the follow-up period, CTA showed no recurrence of rupture or bleeding in all cases. Results of logistic analysis indicated that the transorbital keyhole approach was feasible based on the patients' preoperative Hunt–Hess grades, which should be considered a priority in using this approach in the treatment of ruptured AComA aneurysms.